2002
DOI: 10.1021/es0158004
|View full text |Cite
|
Sign up to set email alerts
|

Task-Specific Ionic Liquids Incorporating Novel Cations for the Coordination and Extraction of Hg2+ and Cd2+:  Synthesis, Characterization, and Extraction Studies

Abstract: A series of hydrophobic task-specific ionic liquids designed to extract Hg2+ and Cd2+ from water were prepared by appending urea-, thiourea-, and thioether-substituted alkyl groups to imidazoles and combining the resulting cationic species with PF6-. The new ionic liquids were characterized and investigated for their metal ion extraction capabilities. When used in liquid/liquid extraction of Hg2+ and Cd2+ from aqueous solutions, the metal ion distribution ratios increased several orders of magnitude, regardles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
260
0
11

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 473 publications
(271 citation statements)
references
References 32 publications
0
260
0
11
Order By: Relevance
“…Most water-immiscible RTILs contain either PF 6 -or bis[(trifluoromethyl)sulfonyl]imide anion ( Table 1). The functionality of the cations was manipulated to coordinate Hg 2+ and Cd 2+ and extract them from water (28). These task-specific ILs incorporate urea-, thiourea-, and thioether-substituted alkyl groups into the imidazolium parent compound, and then this cation is combined with PF 6 -to form the water-immiscible RTIL (Table 1).…”
Section: Extractionsmentioning
confidence: 99%
“…Most water-immiscible RTILs contain either PF 6 -or bis[(trifluoromethyl)sulfonyl]imide anion ( Table 1). The functionality of the cations was manipulated to coordinate Hg 2+ and Cd 2+ and extract them from water (28). These task-specific ILs incorporate urea-, thiourea-, and thioether-substituted alkyl groups into the imidazolium parent compound, and then this cation is combined with PF 6 -to form the water-immiscible RTIL (Table 1).…”
Section: Extractionsmentioning
confidence: 99%
“…[22][23][24][25] Task-specific ionic liquids (TSIL), can extract cations without ion-exchange. [26][27][28] TSILs are ionic liquids with functional groups appended to the cation. Some TSILs appear to be efficient for extraction with high selectivity for some metal ions such as mercury, cadmium, 27,28 or actinides.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] TSILs are ionic liquids with functional groups appended to the cation. Some TSILs appear to be efficient for extraction with high selectivity for some metal ions such as mercury, cadmium, 27,28 or actinides. 26 In this work, we investigate the ability of selected ionic liquids to extract offensive or valuable cations from water.…”
Section: Introductionmentioning
confidence: 99%
“…However, the most important property of ionic liquids that has been exploited in this study is their ability to extract metals from aqueous media (Cruz, 2000;Liu et al, 2005). In this regard, Visser et al (2002) have reported the successful extraction of cadmium (Cd 2+ ) and mercury (Hg 2+ ) from an aqueous medium using ionic liquids via the formation of an IL-metal complex.…”
Section: Scheme 1 An Illustration Of the Inclusion Complex Phenomenonmentioning
confidence: 96%